Polyphenol-rich Morus nigra L. extract mitigates neuroinflammation and cognitive impairment through gut–brain axis modulation in an Alzheimer’s disease rat model - Li, Yue; Zhang, Yangyi; Liu, Mengwen; Dawuti, Tuerxunayi; Chen, Xuanshi; Xiao, Hui (Frontiers in Pharmacology, 2025)
BackgroundThe gut–brain axis (GBA) has emerged as a critical pathway in the pathogenesis of Alzheimer’s disease (AD), offering a potential target for dietary interventions. This study aimed to explore the neuroprotective effects of a polyphenol-enriched extract from Morus nigra L. fruits (MMF) in an AD rat model, focusing on gut-brain communication.MethodsAD-like pathology was induced in rats using a combination of D-galactose and aluminum chloride, followed by a 10-week MMF treatment. Cognitive performance was evaluated using the Morris water maze, and brain Aβ1-42 accumulation and neuroinflammation (Iba1, GFAP) were assessed. Multi-omics approaches, including 16S rDNA sequencing and untargeted colonic metabolomics, were applied.ResultsMMF treatment significantly enhanced spatial memory, reduced hippocampal Aβ burden, and attenuated glial activation. Furthermore, MMF restored gut microbial diversity and increased the abundance of short-chain fatty acid–producing Firmicutes taxa, which were inversely correlated with inflammation. Metabolomics analysis revealed that MMF modulated bile acid and lipid metabolic pathways, with β-muricholic acid, DHA, and ergosterol identified as key effectors.ConclusionMMF alleviates AD pathology through modulation of the gut microbiota and metabolic reprogramming, suggesting a promising microbiota-targeted strategy for AD prevention.